WADAH AKTIVITAS MASYARAKAT DI TANAH SEREAL - Chantika Mayadewi; Dewi Ratnaningrum (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
As social beings, humans naturally need social interaction with others, but often do not have a proper place to support the interaction. Especially in densely populated settlements with limited open space such as in Tanah Sereal, Tambora District, West Jakarta, where community makes the streets and narrow alleys as a place to do various activities. On the other hand, modern times with increasingly evolving technology make society more inclusive and individual, so a facility is needed where residents can carry out joint activities outside the place of residence (first place) and work place (second place) reffered to as the third place that can answer various social needs and urban green spaces in densely populated areas. The method that is used in this study is the conventional method of analysis-synthesis which includes data collection (input), analysis (process), and synthesis (output). Data is obtained from grounded observations, interviews with local residents, literature studies, as well as regional mappings. The third place project in Tanah Sereal is titled Tanah Sereal Commuity Activity Space, which is intended to provide a place of activities for residents of dense settlements in having a shared activity space or a third place that is intergrated with green alley to address social and environmental problems in densely populated areas. The main program of the building is hydroponic planting areas (urban farming), equipped with foodcourt, play areas, teenage discussion areas, communal areas, seminar room, temporary event room, as well as community development program such as hydroponic workshop and garment workshop aimed at improving the skills, productivity, and standard of living of surrounding communities. AbstrakSebagai makhluk sosial, manusia tentunya membutuhkan interaksi sosial dengan sesamanya, namun seringkali tidak memiliki wadah yang layak untuk mendukung terjadinya interaksi tersebut. Terutama di permukiman padat penduduk dengan keterbatasan lahan terbuka seperti di Kelurahan Tanah Sereal, Kecamatan Tambora, Jakarta Barat, di mana masyarakat menjadikan jalan dan gang-gang sempit sebagai tempat untuk melakukan berbagai aktivitas. Di sisi lain, zaman modern dengan teknologi yang semakin berkembang membuat masyarakat menjadi semakin inklusif dan individual, sehingga diperlukan fasilitas di mana warga dapat melaksanakan kegiatan bersama sebagai kegiatan di luar tempat tinggal (first place) dan tempat kerja (second place) disebut sebagai tempat ketiga atau third place yang dapat menjawab berbagai kebutuhan sosial dan ruang hijau kota di kawasan padat penduduk. Pada penelitian ini metode yang digunakan adalah metode konvensional yaitu analisis-sintesis yang meliputi pengumpulan data (input), analisis (proses), dan sintesis (output). Data didapat dari pengamatan grounded ke lapangan, wawancara dengan warga sekitar, kajian literatur, serta mapping kawasan. Proyek third place yang ada di Tanah Sereal ini berjudul Wadah Aktivitas Masyarakat di Tanah Sereal, bertujuan untuk menyediakan sebuah wadah aktivitas bagi warga permukiman padat dalam memiliki ruang aktivitas bersama atau third place yang terintegrasi dengan gang hijau untuk mengatasi permasalahan sosial dan lingkungan di kawasan padat penduduk. Proyek ini memiliki program utama yaitu area tanam hidroponik (urban farming), dilengkapi dengan foodcourt, area bermain, area diskusi remaja, area komunal, ruang seminar, balai serbaguna, serta program pengembangan masyarakat seperti workshop hidroponik dan workshop garmen untuk meningkatkan skill, produktivitas, dan taraf hidup masyarakat sekitar.